THE EFFECT OF PHYSICAL WORK ENVIRONMENT, WORK STRESS AND FINANCIAL COMPENSATION ON EMPLOYEE PERFORMANCE AT PT. YOGAMA PART MANUFACTURING - Rismawati Rismawati; Daspar Daspar (SEAN Institute, 2023)
This study aims to determine whether employee performance affects the physical work environment, work stress and financial compensation, either partially or simultaneously. This research was conducted at PT. Yogama Part Manufacturing with a population of 50 employees. The sampling method used is saturated sampling, which includes all the population as research samples. Data collection techniques include observation, literature study, and distributing questionnaires. The analytical method used is validity, reliability, classical assumption test which includes normality test, multicolinearity, heteroscedasticity, autocorrelation, this analysis method uses multiple regression, namely t and f tests, and coefficient of determination test. Data processing using SPSS 16. The results of the study at the 5% level showed that the physical work environment had a positive and significant effect on employee performance as indicated by the t-count value of 4.409 with a significance of 0.003. Work stress has a positive and significant effect on employee performance as indicated by t count of 4.034 with a significance of 0.000. Financial compensation has a positive and significant effect on employee performance as indicated by the t value of 4.917 with a significance of 0.000. Physical work environment, work stress and financial compensation have a positive and significant effect on employee performance as indicated by the calculated f value of 28,526 with a significance of 0.000. The value of the coefficient of determination is 0.650, which means that the physical work environment, work stress and financial compensation affect employee performance by 65.0% and the remaining 35.0% is influenced by other variables not examined.